2005
DOI: 10.1093/ndt/gfi102
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate can be accurately predicted using lean mass measured by dual-energy X-ray absorptiometry

Abstract: Although further validation is necessary, these findings suggest that total body non-invasive measurement of LM along with Scr can be used to accurately predict GFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Another study carried out in Sweden [9] showed an improvement in the accuracy of eGFR when calculated lean mass was included in the prediction equation. None of these studies have employed the CKD-EPI equation and are limited to relatively small groups of patients or special populations [5,6,7,8,9,10,11,12]. Our study suggests that body composition may also be of importance in the general population but the effect may be of lesser magnitude than in these selected populations.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Another study carried out in Sweden [9] showed an improvement in the accuracy of eGFR when calculated lean mass was included in the prediction equation. None of these studies have employed the CKD-EPI equation and are limited to relatively small groups of patients or special populations [5,6,7,8,9,10,11,12]. Our study suggests that body composition may also be of importance in the general population but the effect may be of lesser magnitude than in these selected populations.…”
Section: Discussionmentioning
confidence: 78%
“…Several previously published studies on the relationship between muscle mass and measured GFR suggest that lean mass might influence eGFR when calculated using the MDRD equation [5,6,7,8,9,10,11,12]. For example, Macdonald et al [10] found that in non-diabetic CKD patients appendicular lean mass index explained an additional 10% of the variability in measured GFR after adjusting for creatinine, age and gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MDRD Study equation might overestimate kidney function in subjects with IUGR, and a possible low-normal kidney function will be veiled, rendering the observed ORs conservative. Formulas including lean body mass could have been well suited for this research question, 30 but information for lean body mass was not available.…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of these equations in Asians, who generally have a smaller body habitus and consequently, different creatinine metabolism than other ethnic groups is unclear [13][14][15][16]. In addition, the utility of the MDRD equation in individuals with normal renal function, diabetic nephropathy or who may vary in glucose tolerance status is still controversial [12,17,18].…”
Section: Introductionmentioning
confidence: 99%